ANALISA KEHILANGAN AIR IRIGASI DI DESA KOTA NEGARA KECAMATAN MADANG SUKU II KABUPATEN OKU TIMUR - Jonizar, Jonizar; Bahri, Zainul; Myka, Adof (Universitas Muhammadiyah Palembang, 2020)
In the irrigation water network in the city village of Negara sub-district of Madang, Suku II, East Oku Regency experienced a significant loss of irrigation water. From the observation site, it is caused by the number of channels that have broken and broken conditions, the growth of wild plants in the walls of the channel and a lot of garbage that has accumulated in the channel and evaporation in the summer. The purpose of this research is to find out how much the loss of irrigation water in the secondary channel starting from the building tapping BGT1 to BGT4 In the liquid that flows in the channel made of concrete over time the channel will be damaged, overgrown with a lot of wild plants because of damage and the other channel will cause water loss during drainage. The source of the data is obtained based on the results of the field survey, primary data and secondary data are obtained.Based on the analysis results, the largest irrigation water loss on the first day in the morning was 0.325 m³ / s, on the sixth day in the afternoon it was 0.332 m³ / s, on the seventh day in the afternoon it was 0.184 m³ / s. The smallest irrigation water loss on the fifth day in the morning was 0.128 m³ / s, the fifth day in the afternoon was 0.129 m³ / s, and the first day in the afternoon was 0.02 m³ / s. The average water loss occurred on the second day with results obtained in the morning of 0.297 m³ / s, in the afternoon amounting to 0.322 m³ / s, and in the afternoon amounting to 0.184 m³ / s.